Leaf trait variation is similar among genotypes of Eucalyptus camaldulensis from differing climates and arises in plastic responses to the seasons rather than water availability. Issue 3 (6th May 2020) - Asao, Shinichi; Hayes, Lucy; Aspinwall, Michael J.; Rymer, Paul D.; Blackman, Chris; Bryant, Callum J.; Cullerne, Darren; Egerton, John J. G.; Fan, Yuzhen; Innes, Peter; Millar, A. Harvey; Tucker, Josephine; et al.
Summary: We used a widely distributed tree Eucalyptus camaldulensis subsp. camaldulensis to partition intraspecific variation in leaf functional traits to genotypic variation and phenotypic plasticity. We examined if genotypic variation is related to the climate of genotype provenance and whether phenotypic plasticity maintains performance in a changing environment. Ten genotypes from different climates were grown in a common garden under watering treatments reproducing the wettest and driest edges of the subspecies' distribution. We measured functional traits reflecting leaf metabolism and associated with growth (respiration rate, nitrogen and phosphorus concentrations, and leaf mass per area) and performance proxies (aboveground biomass and growth rate) each season over a year. Genotypic variation contributed substantially to the variation in aboveground biomass but much less in growth rate and leaf traits. Phenotypic plasticity was a large source of the variation in leaf traits and performance proxies and was greater among sampling dates than between watering treatments. The variation in leaf traits was weakly correlated to performance proxies, and both were unrelated to the climate of genotype provenance. Intraspecific variation in leaf traits arises similarly among genotypes in response to seasonal environmental variation, instead of long‐term water availability or climate of genotype provenance.